2013
DOI: 10.1097/tin.0b013e31829ded8e
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Monitoring and Implementing Evidence-Based Nutrition Practice Guidelines for Type 2 Diabetes Mellitus in 2 Middle Eastern Countries

Abstract: Use of the Academy of Nutrition and Dietetics (Academy) evidence-based nutrition practice guidelines has not been tested internationally. The International Diabetes Outcomes Study explored implementation of the Academy evidence-based nutrition practice guidelines in Turkey and Israel by registered dietitians. The mean hemoglobin A 1c levels decreased from 7.6% to 9.1% at baseline to 6.2% to 7.4% for participants in Turkey and Israel, respectively. Patients at goal increased from baseline to 12 months for low-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“… 4 , 7 Nutrition intervention is a cornerstone of diabetes management to achieve and maintain optimal glycemic and metabolic control and to improve overall health. 6 , 20 Although implementation of the Academy EBNPGs for T2DM has been evaluated in the United States and other countries, 17 , 18 it was unclear whether using the same EBNPGs would yield similar outcomes because of variation in the sample population and the Lebanese health care system compared with the United States. Thus, the aim of the present study was to explore the outcome of implementing the Academy EBNPGs for diabetes in a sample of Lebanese patients newly diagnosed with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 4 , 7 Nutrition intervention is a cornerstone of diabetes management to achieve and maintain optimal glycemic and metabolic control and to improve overall health. 6 , 20 Although implementation of the Academy EBNPGs for T2DM has been evaluated in the United States and other countries, 17 , 18 it was unclear whether using the same EBNPGs would yield similar outcomes because of variation in the sample population and the Lebanese health care system compared with the United States. Thus, the aim of the present study was to explore the outcome of implementing the Academy EBNPGs for diabetes in a sample of Lebanese patients newly diagnosed with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also documented similar improvements in patients' glycemic control and metabolic outcomes following a nutrition intervention. 17 20 A study conducted by Franz et al 19 among 179 American patients with type 2 diabetes reported a reduction in HbA 1C at 6 months compared with the baseline value (among 94 patients who had received a nutrition intervention), and results were used in the creation of the first 2001 Academy of Nutrition and Dietetics Guidelines for T2DM. Likewise, a study by Laitinen et al 21 indicated that compliance with dietary recommendations, following 12 months of intensified nutrition education, led to a reduction in serum lipids in obese patients newly diagnosed with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations